Inovação na educação: autoralidade do aprendiz em uma plataforma educacional - Matoso, Lara Gabriela (2023)
This research problematizes innovation in the context of an educational platform. The objective of the study is to analyze whether the educational platform, in the perception of specialists, enables innovative pedagogical practices that promote student authorship, according to the perspective of the learning paradigm. Human potential is at the heart of the innovation process, and educational systems have the crucial responsibility of nurturing and developing the innovative capacities and possibilities of individuals (ISCHINGER, 2010). It is essential to understand that the innovation process is guided by the skills, knowledge, and attitudes of each individual, and it is the role of education to enhance this set of competencies. This is possible through education for research, in which authorship, authenticity, and student protagonism are among its principles, guaranteed in the learning paradigm (DEMO 2018; 2021). The research developed is of a qualitative field approach and is characterized as exploratory. Data collection was carried out through semi-structured interviews with twelve education professionals, called Specialists, to analyze whether the educational platform (LMS), which has digital tools, allows for innovation in learning relationships. The results showed that, in the perception of the Specialists, the platform is a mediating instrument of innovation because it enables spaces capable of promoting learning, but they understand that it does not produce innovation in itself. They reveal in their perceptions that the platform was built based on a learning logic that promotes student authorship and responsible protagonism. The research aims to contribute to discussions about educational innovations caused by TDICs, according to the Learning Paradigm, and can also provide parameters for the analysis of educational platforms to be implemented in public and private education systems, following the National Policy for Digital Education (NPDE) (BRAZIL, 2023).